Risk Management in Global Supply Chains - Valchev, Zhelyzko (Research Papers, 2020)
Global supply chain risk management is becoming increasingly relevant today, due to the growing roles of increasingly diversified forms of international business, rising global uncertainty and increasing consumer demands and expectations. This study, which focuses on the main aspects of the analyzed process, aims to review existing theories and, based on that, to present a global supply chain risk management solution. For this purpose, the views of a number of international organizations and reputed authors on the topics of sources and risk management tools relevant to the subject of the study are presented. On their basis is introduced an author’s classification of risk types and a concept for risk management in global supply chains.The analysis of existing literature and the development of author’s view are focused on the aspects of international business that affect the analyzed process, thus limiting the topics associated with financial management and classical management theories. Nevertheless, existing literature is extremely rich in a variety of views and theories, and this is the major challenge for creating a complete concept of global supply chain risk management.